Do mergers of large local governments reduce expenditures? - Evidence from Germany using the synthetic control method - Felix Roesel (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
States merge local governments to achieve economies of scale. Little is known to which extent mergers of county-sized local governments reduce expenditures, and influence political outcomes. I use the synthetic control method to identify the effect of mergers of large local governments in Germany (districts) on public expenditures. In 2008, the German state of Saxony reduced the number of districts from 22 to 10. Average district population increased substantially from 113,000 to 290,000 inhabitants. I construct a synthetic counterfactual from states that did not merge districts for years. The results do neither show reductions in total expenditures, nor in expenditures for administration, education, and social care. There seems to be no scale effects in jurisdictions of more than 100,000 inhabitants. By contrast, I find evidence that mergers decreased the number of candidates and voter turnout in district elections while vote shares for populist right-wing parties increased.
urn:nbn:de:bsz:14-qucosa-229858
Keywords: D72; H11; H72; R51; 330; Municipal mergers; Local government; Expenditures; Synthetic control method; Local elections; Voter turnout